Selective Hydrodeoxygenation of Lignin‐Derived Phenolic Monomers to Cyclohexanol over Tungstated Zirconia Supported Ruthenium Catalysts - Gan, Quan; Zhou, Weihao; Zhang, Xueping; Lin, Yamei; Huang, Shenlin; Lu, Guo‐Ping (ChemSusChem, 2024)
The selective hydrodeoxygenation (HDO) of lignin‐derived methoxyphenols to cyclohexanol is one of the most significant transformation in biomass conversion since cyclohexanol is an important industrial raw material. This study has disclosed a series of tungstated zirconia with different Zr/W ratio supported Ru catalysts (Ru/xZrW, x means the molar ration of Zr/W) for the hydrodeoxygenation (HDO) of guaiacol to cyclohexanol. Among these catalysts, Ru/16ZrW has the best catalytic activity, which can achieve 92 % yield of cyclohexanol under the conditions of 180 °C and 1 MPa H2 pressure for 2 h (TOF 231 h−1). Compared with Ru/ZrO2, Ru/16ZrW has smaller particles, more dispersed and electron‐rich Ru species, significant hydrogen spillover and more acid sites, which are the main reason for its excellent performance on this reaction. Apart from guaiacol, other methoxy substitution phenols and organosolv lignin can also be converted into cyclohexanol via hydrodeoxygenation reactions over this catalyst. This study has disclosed a series of tungstated zirconia with different Zr/W ratio supported Ru catalysts (Ru/xZrW, x means the molar ration of Zr/W) for the hydrodeoxygenation of guaiacol to cyclohexanol. Among these catalysts, Ru/16ZrW has the best catalytic activity. Compared with Ru/ZrO2, Ru/16ZrW has smaller particles, more dispersed and electron‐rich Ru species, significant hydrogen spillover and more acid sites.